Drug delivery systems based on biocompatible imino-chitosan hydrogels for local anticancer therapy - Daniela Ailincai; Liliana Tartau Mititelu; Luminita Marin (Taylor & Francis Group, 2018)
A series of drug delivery systems were prepared by chitosan hydrogelation with citral in the presence of an antineoplastic drug: 5-fluorouracil. The dynamic covalent chemistry of the imine linkage allowed the obtaining of supramolecular tridimensional architectures in which the drug has been homogenously dispersed. Fourier-transform infrared spectroscopy (FTIR), wide-angle X-ray diffraction (WXRD) and polarized light microscopy (POM) measurements were used in order to follow the hydrogelation and drug encapsulation processes. The ability of the prepared systems to release the drug has been investigated by UV-Vis spectroscopy using a calibration curve and by fitting the results with different mathematic models. To mimic the behavior of the hydrogel matrix in bio-environmental conditions in view of applications, their enzymatic degradability was monitored in the presence of lysozyme. The in vivo side effects of the systems, in terms of their influence on the blood elements, biochemical and immune parameters were monitored on white Swiss mice by intraperitoneal administration of the injectable obtained hydrogels. All the characteristics of the obtained systems, such as micro-porous morphology, uniform drug encapsulation, enzymatic degradability, lack of side effects, other than the one of the drug itself, along with their ability to release the drug in a sustained manner proved that these material meet the requirements for the development of drug delivery systems, making them suitable for being applied in intraperitoneal chemotherapy.